Correlation between human epidermal growth factor receptor 2 oncoprotein expression and some prognostic factors in papillary thyroid carcinoma - Shervin Rabiee; Mohamadreza Jalali Nadoushan; Neda Mehdizade Rayeni; Iman Ansari (Wolters Kluwer Medknow Publications, 2017)
Background: Thyroid cancer is one of the increasing cancer diagnoses in the United States. Papillary thyroid carcinoma (PTC) is the most common thyroid cancer. There are a few researches done determining the role of human epidermal growth factor receptor 2 HER2 (erbB-2) in PTC prognosis. They also have been controversial. This study is designed to determine the correlation of HER2 expression with tumor size, lymph node involvement, and capsular invasion as prognostic factors. Materials and Methods: This research was a cross-sectional descriptive-analytic study. Information about age, sex, tumor size, and lymph node involvement of 85 patients undergone thyroidectomy and diagnosed PTC in Mostafa Khomeini Hospital during 2010-2012, have been derived from their medical records. Four-micron sections made from paraffin embedded blocks and HER2 expression was assessed by immunohistochemistry. Other sections were stained with H and E Method and capsular invasion was evaluated by microscope. Results: In this study, 88.2% of patients were female and 11.8% of patients were male. About 37.6% of samples were HER2 positive. There was no significant correlation between HER2 and lymph node involvement (P = 0.649), (P > 0.05). A significant correlation found between HER2 and capsular invasion (P = 0.000), (P < 0.05). This study found a significant correlation between HER2 and tumor size (P = 0.000), (P < 0.05). Conclusion: HER2 oncoprotein expression is correlated with increased tumor size and capsular invasion. Hence, HER2 can be used to assess PTC prognosis.